PERILAKU KONSUMEN SMARTPHONE XIAOMI REDMI 1S DI JAKARTA - Billfakkar, Muhammad Fuad; Widyastuti, Dominica A. (Prosiding Seminar Nasional INDOCOMPAC)
This study aimed to examine the effect of price perception and internal quality on purchase decision of Xiaomi Redmi 1s. The data were collected from people who have purchased the Xiaomi Redmi 1s. Primary data is used throughout this study based on 200 respondents who purchased and used Xiaomi Redmi 1s. The data were collected through distribution of structured questionnaires whih used purposive sampling method. Tools of analysis in this study is multiple regression analysis, through the classical assumption and hypothesis test to see relationships between variables either partially or simultaneously. The results showed that price perception and itnernal quality were partially and simultaniously influenced to the purchase decision of Xiaomi Redmi 1s. Keywords : Price perception, internal quality, purchase decision, Xiaomi Redmi 1s